ANALISIS NILAI TAMBAH JERUK NIPIS UNTUK MENINGKATKAN SUBTITUSI EKONOMI PETANI DI DESA SRENGAT KABUPATEN BLITAR - Oryza Sativa, Rima Dewi; Wahyu Budiman, Eko (Universitas Islam Balitar, 2024)
This study aims to determine the condition of lime sales in Srengat village, and to determine the added value of lime sales in Srengat village, Blitar Regency. The current lime sales process is mostly carried out by farmers in Srengat directly without any packaging process. The Business Analysis research method was used in this study. Farming business analysis is used to determine the profit value of selling limes without packaging with packaging. The population or sample of this study were lime farmers and Purposive samples as the data collection technique. Data processing used Farming Business Analysis. Based on the results of the study, it can be concluded that the income received by farmers from the lime commodity is IDR 56,793,200. The income obtained by farmers is greater than the amount of costs that must be incurred to carry out lime farming, so this farming business is declared profitable to do. The R/C Ratio obtained a result of 5.09. This means that every expenditure of IDR 1 can provide an income of IDR 5.09 with the R/C result being 5.09> 1. Showing that lime farming in Srengat Village is profitable and feasible to develop. The added value obtained from handling packaged limes is Rp 66,230,000 with a ratio of 6.14 percent. Based on the analysis of the farming business, it can be concluded that selling packaged limes will provide greater profit value compared to selling without packaging. Analysis of added value in post-harvest lime activities shows that the greater the added value given to a product, the greater the profit obtained.